Changes in metabolism of cerebral glucose after stereotactic leukotomy for refractory obsessive-compulsive disorder: a case report. Issue 4 (April 1995) - Biver, F; Goldman, S; François, A; De La Porte, C; Luxen, A; Gribomont, B; Lotstra, F
Abstract : Brain glucose metabolism was investigated with PET and [18F]fluorodeoxyglucose, before and after a bifrontal stereotactic leukotomy in a 37 year old woman with refractory obsessive-compulsive disorder. A bilateral decrease in glucose metabolism was found in the orbital frontal cortex after psychosurgery. Glucose metabolism was decreased to a lesser degree in Brodmann's area 25, in the thalamus, and in the caudate nucleus. Clinical improvement in obsessive-compulsive disorder after stereotactic tractotomy seems to be associated with metabolic changes in the brain, in particular, in the orbital part of the frontal lobe.